(untitled) (Revista Ciência Agronômica, 2017)
Maintenance of crop residues over soil surface under conservational systems limits incorporation of nitrogen fertilizers into the soil. Application of urea over crop residues enhance N-NH3 volatilization losses, justifying the usage of urease inhibitors or N sources less susceptible to volatilization under such conditions. This study aimed to evaluate volatilization losses from N sources applied over sugarcane straw. A field trial was carried out in a sugarcane field in Iracemapolis, Sao Paulo on a Typic Kandiudox in June 2014. We used a complete block experimental design, with seven treatments and four replications. Treatments included Control [CO], ammonium nitrate [AN], NS30TM (ammonium nitrate-75% and ammonium sulfate-25% fused mixture) [NS30TM], ammonium nitrate plus ammonium sulfate (ammonium nitrate-75% and ammonium sulfate-25% physical mixture) [AN-AS], urea [UR], urea treated with 0.4% Cu and 0.15% B [UR-CuB], urea treated with 530 mg kg-1 of NBPT [UR-NBPT]. Treatments were applied at rate of 100 kg ha-1 N (except CO). Volatilization losses were quantified up to 30 days after fertilization (DAF). Maximum N-NH3 occurred 16 DAF for UR and UR-CuB and 20 DAF for UR-NBPT. Accumulated N-NH3 losses ranged from 20% (UR), 17% (UR-CuB), and 14% (UR-NBPT) of applied N; nonamidic sources showed losses lower than 1%. Adding urease inhibitor to urea shows potential in reducing volatilization losses even under application over large amounts of straw.